Response Strategies to Legal Risks of Big Data-Enabled Digital Economy: -- Based on Beijing-Tianjin-Hebei Synergistic Development - Li, Xiangyu (Transactions on Economics, Business and Management Research, 2024)
Under Beijing-Tianjin-Hebei's strategy of its simultaneous development, the digital economy with its networked, digitised and intelligent industrial operations is developing rapidly, and big data is both the object of its production and creation, and can also provide legal protection for the digital economy. Although the use of big data in practice is gradually increasing, it has not been fully embraced at the legislative, law enforcement and judicial levels as an adaptive means of safeguarding the digital economy. Big data can promote digital industrialisation and industrial digitisation, help digital rights and maintain intellectual property rights, regulate the platform economy against monopoly and unfair competition, accelerate data sharing and help protect personal information, can effectively make up for the existing laws and regulations and the traditional regulatory model of the digital economy of the soil and soil, so the law to absorb big data to solve the risks of the digital economy is imperative. Big data should be based on the different needs of criminal, civil and administrative laws, respectively; legislation for high-tech crimes, protection of personal information and intellectual property rights; law enforcement for the platform economy, anti-monopoly and anti-unfair competition, and tax evasion; and judiciary for the evidence of big data, the introduction of talents and smart work models, to build a legal risk response strategy for the synergistic development of the digital economy empowered by big data.